Strengthening of Student Character Through Values-Based Learning of Prince Antasari's Struggle Character - Dian Agus Ruchliyadi; Rabiatul Adawiah (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
Various problems related to the nation's moral decadence are still very concerning, especially the problems that affect the younger generation. One effort to overcome these problems is through education. This study aims to determine the effectiveness of learning based on the values ​​of the character of the struggle of Prince Antasari in shaping the character of students. The research was conducted at the Banjarmasin City High School. This research is a quantitative research with quasi-experimental methods. The results of this study indicate that the application of the Pancasila and Citizenship Education learning model based on the values ​​of Prince Antasari's fighting character has a significant influence on strengthening the character of students. The implications of using the Pancasila Citizenship Education learning model based on the values ​​of the character of Prince Antasari's struggle for these learning outcomes certainly correlate with the achievement of the learning objectives to be achieved, especially in the affective domain. Through a model orientation based on character values ​​from the struggle of a figure, it can be used as a form of treatment in learning values ​​and character building which involves the active participation of students in the implementation of learning activities